2023
DOI: 10.58661/ijsse.v3i1.109
|View full text |Cite
|
Sign up to set email alerts
|

How Employee Conflict Behavior Affects Work Engagement: Transformational Leadership as Mediator and Moderating role of Pro-Social Motivation

Abstract: The objective of this study is to assess the effects of a follower’s conflict behavior (FCB) on work engagement (WE), as well as how transformational leadership (TL) governs the link between dimensions of FCB problem-solving behavior (PSB), dominating conflict behavior (DCB) with WE and moderating impact of prosocial motivation on the relationship between dimensions of followers’ conflict behavior (PSB & DCB) with TL. Data was collected using a quantitative technique and a cross-sectional survey method fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This research also makes an addition by examining the conflict behaviors of followers as mediators between the conflict and the leadership styles (transformational leadership, transactional leadership, and laissez-faire leadership), it is found that dominating conflict behavior act as a mediator in the relationship between laissez-faire leadership styles and both relationship and task conflict. However, in a manner with relationship conflict, it governs the relationship due to considering own perspective and ignoring other as the theory of conflict handling styles (Rahim, 1983) also support the argument and validate the results, however, no research has been found in using dominating conflict behavior as a mediator but this term is also used as a novel approach in conflicting researches and exhibited negative outcomes (Asim & Siddiqui, 2023a;Aw & Ayoko, 2017). As far as the mediation with task conflict is concerned, it has been found in contributing as a mediator, it is important to note that dominating behavior is generally not considered an effective or constructive approach for enhancing task conflict.…”
Section: Managerial Implicationsmentioning
confidence: 67%
“…This research also makes an addition by examining the conflict behaviors of followers as mediators between the conflict and the leadership styles (transformational leadership, transactional leadership, and laissez-faire leadership), it is found that dominating conflict behavior act as a mediator in the relationship between laissez-faire leadership styles and both relationship and task conflict. However, in a manner with relationship conflict, it governs the relationship due to considering own perspective and ignoring other as the theory of conflict handling styles (Rahim, 1983) also support the argument and validate the results, however, no research has been found in using dominating conflict behavior as a mediator but this term is also used as a novel approach in conflicting researches and exhibited negative outcomes (Asim & Siddiqui, 2023a;Aw & Ayoko, 2017). As far as the mediation with task conflict is concerned, it has been found in contributing as a mediator, it is important to note that dominating behavior is generally not considered an effective or constructive approach for enhancing task conflict.…”
Section: Managerial Implicationsmentioning
confidence: 67%
“…Recent research has taken steps to categorize different styles of conflict resolution, most notably integrating, compromising, competing, avoiding, and obliging styles (Rahim, 1983). However, existing literature often examines these conflict-handling styles in isolation, leaving a gap in understanding how combinations of these styles, or what we term as 'problem-solving behavior,' 'dominating conflict behavior,' and 'non-confronting conflict behavior' (Mubashir & Siddiqui, 2023a;Aw & Ayoko, 2017a) might differentially impact work stress. Our novel categorizations aim to encapsulate more realistic, nuanced ways individuals may approach conflict.…”
Section: Introductionmentioning
confidence: 99%